2019
DOI: 10.7717/peerj.6383
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin protects rat against myocardial ischemia/reperfusion injury by modulating the mitochondrial apoptosis pathway

Abstract: BackgroundTaxifolin (TAX), is an active flavonoid, that plays an underlying protective role on the cardiovascular system. This study aimed to evaluate its effect and potential mechanisms on myocardial ischemia/reperfusion (I/R) injury.MethodsHealthy rat heart was subjected to I/R using the Langendorff apparatus. Hemodynamic parameters, including heart rate, left ventricular developed pressure (LVDP), maximum/minimum rate of the left ventricular pressure rise (+dp/dtmax and −dp/dtmin) and rate pressure product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
4
13
0
1
Order By: Relevance
“…There are no studies in the literature on the effect of taxifolin on LPO in cochlear tissue. However, recent studies have shown that taxifolin inhibits MDA increase in blood serum and heart tissue (20,21). This information obtained from the literature shows that previous studies support the results of our biochemical and histopathological experiments.…”
Section: Histopathological Resultssupporting
confidence: 91%
“…There are no studies in the literature on the effect of taxifolin on LPO in cochlear tissue. However, recent studies have shown that taxifolin inhibits MDA increase in blood serum and heart tissue (20,21). This information obtained from the literature shows that previous studies support the results of our biochemical and histopathological experiments.…”
Section: Histopathological Resultssupporting
confidence: 91%
“…El doble producto (DP) se encuentra disminuido en los procesos de isquemia reperfusión [9] y esto quedó demostrado en la DO del corazón perfundido a la velocidad de 10.5mL/min, en donde, al minuto 70, disminuyó hasta un valor de 10361 ± 2260, en comparación con el control que mantiene un valor de 22391 ± 2286 (Fig 1C). En la figura 1D se representan los resultados del doble productos para corazones sometidos a una perfusión a 12 mL/ min.…”
Section: Resultados a Determinación De Los Parámetros Cardiacosunclassified
“…It inhibits the activity of oxidases reducing excessive production of reactive oxygen species (ROS). As it can reduce oxidative stress damage, it can improve rat ischemia-reperfusion injury by inhibiting the mitochondrial apoptosis pathway [ 39 ]. Sun et al found that TAX can improve diabetic cardiomyopathy by regulating oxidative stress and apoptosis in cardiomyocytes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%